Integrating transcriptome and metabolome to explore the growth-promoting mechanisms of GABA in blueberry plantlets - Liu, Mingfeng; Bai, Mingyue; Yue, Jiajia; Fei, Xiaoke; Xia, Xiuying (Frontiers in Plant Science, 2023)
Tissue culture technology is the main method for the commercial propagation of blueberry plants, but blueberry plantlets grow slowly and have long growth cycles under in vitro propagation, resulting in low propagation efficiency. In addition, the long culturing time can also result in reduced nutrient content in the culture medium, and the accumulation of toxic and harmful substances that can lead to weak growth for the plantlets or browning and vitrification, which ultimately can seriously reduce the quality of the plantlets. Gamma-aminobutyric acid (GABA) is a four-carbon non-protein amino acid that can improve plant resistance to various stresses and promote plant growth, but the effects of its application and mechanism in tissue culture are still unclear. In this study, the effects of GABA on the growth of in vitro blueberry plantlets were analyzed following the treatment of the plantlets with GABA. In addition, the GABA-treated plantlets were also subjected to a comparative transcriptomic and metabolomic analysis. The exogenous application of GABA significantly promoted growth and improved the quality of the blueberry plantlets. In total, 2,626 differentially expressed genes (DEGs) and 377 differentially accumulated metabolites (DAMs) were detected by comparison of the control and GABA-treated plantlets. Most of the DEGs and DAMs were involved in carbohydrate metabolism and biosynthesis of secondary metabolites. The comprehensive analysis results indicated that GABA may promote the growth of blueberry plantlets by promoting carbon metabolism and nitrogen assimilation, as well as increasing the accumulation of secondary metabolites such as flavonoids, steroids and terpenes.